Reedição e retradução contra o racismo: análise de "And then there were none" de Agatha Christie - Alves-Alcântara, Fernanda Araújo (2023)
This study investigates the racism in literature and methods that include retranslation as a tool to remove the racism and the polysystem theory associated with descriptive translation studies to explain the reasons why some books are being questioned. In the analysis chapter, the 5 editions of the book “And Then There Were None” by Agatha Christie are contrasted by the principles of translation studies and anti-racist literature. The trajectory of the book was considered controversial due to the various updates made in order to remove racist aspect. In order to succeed in the proposed objective, we settled on bibliographical research with an exploratory-explanatory character and a qualitative approach. The theoretical basis was made from relevant intellectuals of Translation Studies, as Berman (1990), Gambier (1994) and (2013) for retranslation theories; Lefevere (2007) and (1992) with concepts of rewriting; Jakobson (1969) and intralingual studies; Even-Zohar (1997), (2005) e (2013) for polysystem theory and Toury (2012) for descriptive translation studies. The theoretical basis of anti-racist authors such as Lélia Gonzalez (1982), Djamila Ribeiro (2019), Silvio de Almeida (2018), Carolina de Jesus (2014) and Clóvis Moura (2014) was also used. Regarding to the obtained results, there is a change of paradigms about the acceptance of literature, the society don’t accept the perpetuation of expressions that hurt the reader, it cannot remain unchanged. In our current polysystem, many authors and books are being criticized because they support racial stereotypes, requiring retranslation resources to avoid the banning of canonized books.